Modelagem para a mensuração do desempenho das capacidades de inovação de startups inteligentes - Kaczam, Fabíola (2019)
The technological acceleration, required by the process of transition to the smart industry, reinforces the importance of smart startups. After verifying, based on the literature, that startups face difficulties in the management of innovation capacities, the present dissertation had as objective to develop a modeling able to measure the performance of the innovation capacities for smart startups. Measuring innovation capabilities allows startups to recognize themselves in the current scenario, addressing the demands of the smart industry and driving decision-making to achieve an innovative performance. As for the methodological assumptions adopted, this is an exploratory, descriptive and cross-sectional research, of an applied and ex post facto nature with an inductive scientific method; of qualitative and quantitative approach, in which the technical procedures comprise bibliographical, documentary and survey research. A total of 33 performance indicators were collected. For this, the Key Performance Indicators (KPI) assumptions, as well as the methodological support of Analytic Hierarchy Process (AHP) elements were used. A proposed collection instrument was applied in 36 startups, of which 24 met the selection criteria for the modeling application, which returned to them the respective overall performance, as well as the performance in each of the four points of view that comprise the innovation capabilities. In addition to the discussion of results about the performances obtained, a simulation was performed from the data of a startup with an unsatisfying overall performance, in which three situations were projected, demonstrating the evolution in the performance from actions directed to the specific indicators. As support for modeling, with the help of Microsoft Office Excel® spreadsheet and the Visual Basic for Applications® (VBA) programming language, in order to complement the general objective, a tool has been developed. It allows the collection and processing of data, in addition it allows updating indicators and evaluation scales. In this way, it can be verified the fulfillment of the general and specific objectives. With regard to the contributions, this research can be considered as the starting point to conceptualize the smart startups, demonstrating that although the origin of the smart industry concept being the manufacturing environment, the enabling technologies can be applied in other models of business.